1984
DOI: 10.1128/mcb.4.6.1175
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation of MAP-2 stimulated by calcium-calmodulin and cyclic AMP.

Abstract: Comparison of cyclic AMP-and calcium-dependent phosphorylation in rat brain cytosol reveals MAP-2 to be a common endogenous substrate. Examination of limited protease digestion patterns indicates that the two kinases phosphorylate MAP-2 at distinct sites and suggests that such phosphorylation may have differential effects on MAP-2 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The demonstration in this report that microtubule preparations contain an endogenous calmodulin-dependent MAP 2 kinase indicates that both calmodulin-and cAMP-dependent kinases may play a role in regulating microtubule function. A previous report indicated that a purified calmodulin-dependent kinase phosphorylated distinct sites on MAP 2 compared to cAMP-dependent kinase (26). In the present report, the endogenous calmodulindependent kinase in the void fraction incorporated at least 5 mol of phosphate per mol of endogenous MAP 2.…”
Section: Resultssupporting
confidence: 58%
“…The demonstration in this report that microtubule preparations contain an endogenous calmodulin-dependent MAP 2 kinase indicates that both calmodulin-and cAMP-dependent kinases may play a role in regulating microtubule function. A previous report indicated that a purified calmodulin-dependent kinase phosphorylated distinct sites on MAP 2 compared to cAMP-dependent kinase (26). In the present report, the endogenous calmodulindependent kinase in the void fraction incorporated at least 5 mol of phosphate per mol of endogenous MAP 2.…”
Section: Resultssupporting
confidence: 58%
“…There is very little data on the precise location of endogenous phosphorylation sites in MAP2 . Both cAMP-dependent and Cal+/calmodulin kinases have been shown to phosphorylate sites in the portion of the molecule that is bound to microtubules (Vallee, 1980;Schulman, 1984 ;Vallano et al ., 1985 ;Hernandez et al, 1987) . However, it is clear that the degree of phosphorylation of all in vitro preparations is less than that of MAP2 in the living brain (Tsuyama et al, 1987), and other phosphorylation sites might exist that also influence the interaction of MAP2 with microtubules .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro studies have shown that the phosphorylation of MAPs prevents them from functioning to promote microtubule assembly, thus, resulting in disassembly or increased flux of microtubules (16,17). Furthermore, Schulman (34) has reported that the phosphorylation of MAP-2 is stimulated by a Ca2÷-CaM-dependent kinase in vitro. Thus, a precedent for such a mechanism in the mitotic spindle exists.…”
Section: Discussionmentioning
confidence: 99%